Media Kotak Kata terhadap Kemampuan Membaca Permulaan pada Anak Slow Learner - Fatih, Ifan Abdillah; Ariyanto, Dedy; Megaswarie, Rosika Novia (JOEAI (Journal of Education and Instruction), 2025)
This study aimed to investigate the impact of using word boxes on early reading skills in students with slow learning abilities. The method used was a Single-Subject Research (SSR) design with an A-B design, comparing conditions before (baseline) and after the intervention. The results showed that using word boxes improved early reading skills in students who are slow learners. The conclusion of this study is that word boxes are an effective learning tool in developing early reading skills in slow learners, as evidenced by a 0% overlap in all data obtained.   Keywords: Word Box, Slow Learners